2006
DOI: 10.1111/j.1747-6593.2006.00018.x
|View full text |Cite
|
Sign up to set email alerts
|

A proposal for managing wastewater in Harare, Zimbabwe

Abstract: This paper deals with wastewater management in Harare, in the Lake Chivero catchment area of Zimbabwe. It aims at developing a sustainable system for managing water and nutrients and is based on the literature and a water quality monitoring study conducted from June 2000 to December 2001. This study has shown serious water pollution problems due to urbanisation in the catchment. A 'three-step strategic approach' to urban (waste)water management was used as a basis for formulating solutions. The short-term solu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 5 publications
0
13
0
Order By: Relevance
“…In fact, most parts in the city of Kampala (> 90 %) as well as other urban areas in SSA (> 70 %) are largely unsewered (Nyenje et al, 2010) implying that most people living in these areas rely on on-site sanitation for wastewater disposal. However, due to poor on-site sanitation systems especially in slum areas (Kulabako et al, 2007;Nyenje et al, 2013a;Isunju et al, 2011;Katukiza et al, 2010), most wastewater generated in the catchment ends up into the drainage system hence introducing a number of pollutants and nutrients to downstream ecosystems.…”
Section: Catchment Descriptionmentioning
confidence: 99%
See 4 more Smart Citations
“…In fact, most parts in the city of Kampala (> 90 %) as well as other urban areas in SSA (> 70 %) are largely unsewered (Nyenje et al, 2010) implying that most people living in these areas rely on on-site sanitation for wastewater disposal. However, due to poor on-site sanitation systems especially in slum areas (Kulabako et al, 2007;Nyenje et al, 2013a;Isunju et al, 2011;Katukiza et al, 2010), most wastewater generated in the catchment ends up into the drainage system hence introducing a number of pollutants and nutrients to downstream ecosystems.…”
Section: Catchment Descriptionmentioning
confidence: 99%
“…Zhang et al (2007) found a TP flux of only 0.034 kg km −2 d −1 in nutrient runoff from forested watershed in central Japan. Nhapi et al (2006) showed that the TP flux for the two major river inflows to the eutrophic Lake Chievero in the city of Harare (Zimbabwe) ranged between 0.1 and 0.35 kg km −2 d −1 . Although these rivers were heavily polluted by on-site sanitation and sewage overflows from treatment plants, the TP fluxes were still low when compared to those in our study.…”
Section: Phosphorus Exported From the Catchmentmentioning
confidence: 99%
See 3 more Smart Citations